Whom Do We Serve: Doctoral Research in Library and Information Science in India - Satija, M.P. (DESIDOC Journal of Library & Information Technology, 2003)
Discovery and dissemination of new knowledge has always been a source of excitement and incalculable social benefit to the society. Tremendws progress made by the mankind in the 20th century is only due to research and new information. Information society subsists on information which is only generated by research. This article briefly describes the beginning, growth of doctoral research and proliferation of education in Library and information Science {LIS) in India. Author's views on the status and quality of research in LIS in lndia have also been given. http://dx.doi.org/10.14429/dbit.18.1.3383